In vitro cellulose disappearance of brewery waste incorporated paddy straw based Feeds in rusitec: In vitro cellulose disappearance of brewery waste incorporated paddy straw based Feeds in rusitec - Senthilkumar, S (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An in vitro experiment was conducted to study the in vitro cellulose disappearance of the following seven experimental feeds such as 1) Control feed; 2) Experimental feed (75%) + Fresh brewery waste (25%) (EFFBW); 3) Experimental feed (75%) + Dried brewery waste (25%) (EFDBW); 4) Fresh brewery waste (FBW); 5) Dried brewery waste (DBW); 6) Paddy straw (PS) and 7) Brewery waste incorporated paddy straw (BWIPS) incubated for 2, 6, 12, 24, 48 and 72 hours in Rumen Simulation Technique (RUSITEC). During initial incubation periods (2, 6, 12 and 24 hours), control feed, EFFBW, EFDBW and FBW showed higher in vitro cellulose disappearance than other experimental feeds, whereas, during later incubation periods (48 and 72 hours), the DBW, paddy straw and BWIPS showed higher in vitro cellulose disappearance than other experimental feeds incubated in RUSITEC. Among the feeds experimented in RUSITEC, disappearance of cellulose was more in the control feed, EFFBW and EFDBW when compared to other experimental feeds. Similarly, the cellulose disappearance was more in BWIPS compared to paddy straw. The in vitro cellulose disappearance rates at all incubation periods were higher for FBW than those for DBW.